Peristilahan dalam Menangkap Ikan Tradisional pada Masyarakat Dayak Ketungau Sesat: Kajian Semantik - Pabianus Simon (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research focuses on the terminology in fishing in the Dayak Ketungau Sesat community. The fishing tradition in question is still traditional in terms of both tools and processes. The method used in this study is descriptive. The data in this study are in the form of terminology contained in the fishing tradition in the Dayak Ketungau Sesat community. Based on the results of the research conducted, the researcher managed to collect 49 terms consisting of 5 classifications. The data are based on the classification of tools as many as 13, based on the classification of tool part names as many as 4, based on the classification of materials as many as 11, based on the classification of processes as many as 13, and based on the name of the place as many as 8 terms.